Review of Milena B. Methodieva, Empire and Nation: Muslim Reform in the Balkans - Naxidou, Eleonora (Historein, 2023)
Review of Milena B. Methodieva, Empire and Nation: Muslim Reform in the Balkans (Stanford: Stanford University Press, 2021), 331 pp.